Toward an Emotioncy Based Education: A Systematic Review of the Literature - Miri, Mir Abdullah; Pishghadam, Reza (Frontiers in Psychology, 2021)
The current systematic review summarizes the growing body of literature on the concept of emotioncy. It presents a synthesis of 61 studies discussing emotioncy related topics. The aims were to examine, interpret, and synthesize results about emotioncy to generate an in-depth and holistic discussion of the key routes of emotioncy based education and the different influencing factors at policy and practice levels. The review revealed that emotioncy has been explored in different disciplines, particularly English language teaching, Persian language teaching, neuroscience, and psychosociology. It was shown that although both empirical and theoretical studies have been conducted on emotioncy, there is abundant room for future studies to use various research methodologies and scopes. The review offers a few data-driven pedagogical implications on emotioncy-based education. The authors argue that emotioncy warrants closer scrutiny in different disciplines.